Mobilities, Migration and Identities in Selected Zimbabwean Fictional Narratives - Saneliso, Thambo (My University, 2018)
This study examines the representation of the Zimbabwean migrant experiences in both regional and international migrations. It utilizes narratives that highlight the experiences of the Zimbabweans who migrate thereby exploring issues of mobility and identity. These narratives are Harare North (2010), An Elegy for Easterly (2010), Zebra Crossing (2013), We Need New Names (2014) and The Maestro, The Magistrate and The Mathematician (2014). These narratives have been utilized in the study to argue that migrants encounter traumatic experiences as they cross either the regional or international spaces they move to in search of better economic prospects. It further explores the kinds of trauma that they are subjected to, ranging from racism, the threat and reality of xenophobic attacks, the intricacy of negotiating an existence and a livelihood in these new spaces, searching for employment, to mention a few. The study argues that the migration experience has a catastrophic effect on the migrants’ psychological state, represented as partially being caused by the realization that the host country presents its own set of challenges and is also hostile, a different reality from the preconceived romanticized view of the countries they migrate to. The study argues that the selected novels foreground the inhospitable nature of the Zimbabwean post-2000 political instabilities and the socio-economic meltdown as fostering the forced trans-migrations of Zimbabweans in an effort to escape poverty and political challenges.
MA (English)
Department of English
Keywords: Bulawayo; UCTD; Chikwava; Gappah; Home; Huchu; Identity; Mobilities; Migration; Vandermerwe; Zimbabwe; 809.88996891; Shona literature -- History and criticism; Zimbabwe literature (English); Zimbabwe -- Social conditions; Zimbabwean fiction -- History and criticism; Zimbabwe fiction (English)